Improving the technical training of qualified athletes in acrobatic rock and roll - Батєєва [Nataliya Batieieva], Наталья Петровна; Кизим [Petro Kуzim], Петро Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> On the basis of biomechanical analysis of competitive exercise «2/4 salto Front Layout to catch» The technique of improving the technology of the acrobatic elements in the acrobatic rock'n'roll. Using the proposed method led to improved technical training of qualified athletes category «Main-class» in the acrobatic rock and roll studied kinematic characteristics acrobatic movements in rock'n'roll. Determine the total force and a separate partner and the partner applied when the competitive element of «2/4 salto Front Layout to catch» an acrobatic rock'n'roll. First Point of algorithms for computing the force applied by the joint implementation of competitive activity «2/4 salto Front Layout to catch» may be recommended for the development and improvement of the technique of the movement of any unsupported sportive couple in the acrobatic rock'n'roll. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->